Study of Drought Tolerance of Some Durum Wheat (Triticum durum Desf.) Genotypes Growing under Semi-arid Conditions in Algeria - Frih, Benalia; Oulmi, Abdelmalek; Guendouz, Ali (International Journal of Bio-resource and Stress Management, 2021)
The aim of this study was to test the behavior of 5 genotypes cultivated in normal and irrigated conditions with regard to drought stress. We used seven indices of tolerance and resistance to drought stress. Analyze of variance showed that the geometric mean productivity, mean productivity, stress tolerance index, yield stability index, stress sensitivity tolerance and tolerance intensity were effective in judging tolerance to water stress, Boussellem and Oum Rabie was the best at water stress resistance genotypes. Correlation analysis showed that GMP is both an indicator of high performance under both conditions and of resistance to stress (r=0.56* in a stress state and r=0.82*** in a non-stress state) . Boussellem and Oum Rabie were the strongest in yield and the most adapted to water stress thanks to their values ​​for this index (8.84 and 9.06 respectively). SSI testified to the high yield in non-stress condition (r=0.82***), therefore Ofanto was a good cultivar in non-stess condition. PCA classified the genotypes Bousselem and Oum Rabie on the first component which combined the performance in yield under both conditions with the mean productivity, geometric mean productivity, and stress tolerance index. In conclusion, the Oum Rabie and Bousselem genotypes were the best performing under both conditions and the best adapted to drought stress, while Ofanto was a good cultivar in non-stress conditions. MP, GMP and STI indices was the best to judge the adaptability of our genotypes to drought stress.